Autologous transobturator sling as an alternative therapy for stress urinary incontinence. Issue 3 (1st April 2019) - Laufer, Joel; Scasso, Santiago; Bentancor, Valeria; Bertoche, Cecilia; Sosa, Claudio G.; Elliott, Daniel S.
Abstract: Objective: To evaluate efficacy and outcomes of the autologous transobturator midurethral sling for treatment of stress urinary incontinence (SUI). Methods: In a prospective cohort study, an autologous transobturator mid‐urethral sling was used to treat SUI among women attending a university hospital in Montevideo, Uruguay, from June 2017 to July 2018. In the first phase, autologous tissue of the abdominis rectus fascia was collected. In the second phase, the midurethral sling was placed via the transobturator approach. Outcomes were measured every 3 months by the International Consultation on Incontinence Questionnaire Female Lower Urinary Tract Symptoms (ICIQ‐FLUTS) Score. Preoperative and postoperative results were compared by Wilcoxon test. Results: Eighteen women with a median age of 51 years were enrolled. The median follow‐up was 9 months (range 6–15 months). Overall, 17 women showed symptomatic improvement after the procedure. In a comparison of preoperative versus postoperative ICIQ‐FLUTS questionnaires, improvement in the incontinence subscore was observed at 3 ( P <0.001), 6 ( P <0.001), and 12 ( P =0.008) months. No severe complications were observed. Conclusion: Use of an autologous transobturator urethral sling was found to be technically feasible and safe for SUI, with good short‐term outcomes. Longer follow up and larger series are needed to validate the procedure. Abstract : Autologous transobturator sling was found to be an effective technique that should be considered for the treatment of stress urinary incontinence.